The interaction of regulated forms of cell death in the pathogenesis of severe facial paralysis and potential therapeutic strategies - Tang, Xing; Ji, Ziqin; Xiao, Xueling; Zhu, Tongtong; Lan, Shoujen; Yen, Yeayin; Shao, Xin; Tan, Shune; Wang, Chao; Zhang, Jicheng (Frontiers in Neuroscience, 2025)
Neuronal cell death plays a central role in the pathogenesis of facial paralysis. In the constructed severe facial paralysis model, axonal damage becomes the key factor triggering retrograde neuronal degeneration, resulting in a large number of neuronal deaths, which seriously affects the function of the facial nerve. The basic fibroblast growth factor exhibits strong neuroprotective ability and can significantly reduce the neuronal mortality rate, providing a strong guarantee for neuronal survival. Viral infection is also an important pathogenic factor that cannot be ignored. Viruses such as herpes simplex virus type 1 can trigger neuroinflammation through the immune response, further exacerbating nerve damage. However, recent studies have also brought hope. Neural reconstruction techniques, targeted drugs, and stem cell therapies hold potential value in promoting the recovery of damaged neural functions. These research results reveal that multiple factors affect the survival and function of neurons in facial paralysis through different pathways, laying a theoretical foundation for targeted treatment against neuronal death. In the future, based on these mechanisms, developing new therapies will bring new treatment opportunities for patients with severe facial paralysis, potentially improving their prognosis and significantly enhancing their quality of life, with important clinical value.